تقدير المعالم الوراثية للحاصل ومكوناته في الحنطة (.Titicum spp) - علي, اسماعيل حسين (Sulaimani Journal for Pure and Applied Sciences, 2002)
Genetical parameters of yield and its components, correlation relations and partial regression were estimated by using ten wheat varieties Triticum spp. In RCBD experiment during 98-1999 in college of Agric. Univ. of DOHUK Genetic variability was high between varieties for all characters except spike length with reduction of environmental variance, s the heritability and expected genetic advance increased particularly of spikes/plant which had appositive relation in regard of genetic and phenotypic correlation significantly with grain yield was (0.741) and (0.712) respectively. This results had been supported by partial regression analysis which showed that grain yield dependent mainly on spikes / plant. Therefore there is possibility of improving grain yield by selection of one of its component.
Keywords: الحنطة المعلم الوراثیة تحلیل الانحدار